PENGARUH EKSPOR KELAPA SEGAR DAN KELAPA KERING TERHADAP INDUSTRI OLAHAN KELAPA (STUDI KASUS : PROVINSI RIAU) - Evi Christanty Pasaribu; Den Yealta (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This study discusses about how fresh coconut and desicatted coconut export can affect the coconut industry in Riau Province, the largest producer coconut in Indonesia as the case study. Since 2011-2017 the export of fresh coconut and desicatted coconut showed fluctuations. The coconut areas continue to decrease followed by the reduce of production, with the amount of fresh coconut exports in large numbers causing the coconut industry has short of coconut raw material to produce various coconut products which has higher selling value. The coconut industries are difficult to produce various product of coconut that has higher selling value, the number of coconut industry has declined and the competitive point of coconut industry is low. This study shows that an integrative partnership is needed between coconut farmer, coconut entrepreneurs (coconut processing factories) and the government to improve the condition of the coconut industry in Riau Province. Keywords: Export, Fresh Coconut, Desicatted, Coconut Industry, Coconut Farmer, Effect, Riau Province.